By any media necessary : the new youth activism - Jenkins, Henry, 1958- (New York : New York University Press, 2016)
"There is a widespread perception that the foundations of American democracy are dysfunctional and little is likely to emerge from traditional politics that will shift those conditions. Youth are often seen as emblematic of this crisis--frequently represented as uninterested in political life and ill informed about current affairs. By Any Media Necessary offers a profoundly different picture of contemporary American youth. Young men and women are tapping into the potential of new forms of communication, such as social media platforms and spreadable videos and memes, seeking to bring about political change--by any media necessary. In a series of case studies covering a diverse range of organizations, networks, and movements--from the Harry Potter Alliance, which fights for human rights in the name of the popular fantasy franchise, to immigration-rights advocates using superheroes to dramatize their struggles--By Any Media Necessary examines the civic imagination at work. Exploring new forms of political activities and identities emerging from the practice of participatory culture, By Any Media Necessary reveals how these shifts in communication have unleashed a new political dynamism in American youth."--Jacket.
Youth voice, media, and political engagement : introducing the core concepts / Henry Jenkins -- "Watch 30 minute video on Internet, become social activist?" : Kony 2012, invisible children, and the paradoxes of participatory politics / Sangita Shresthova -- "Decreasing world suck" : harnessing popular culture for fan activism / Neta Kligler-Vilenchik -- Between storytelling and surveillance : the precarious public of American Muslim youth / Sangita Shresthova -- DREAMing citizenship : undocumented youth, coming out, and pathways to participation / Liana Gamber-Thompson and Arely M. Zimmerman -- Bypassing the ballot box : how libertarian youth are reimagining the political / Liana Gamber-Thompson -- "It's called giving a shit!" : what counts as "politics"? / Henry Jenkins and Sangita Shresthova -- Afterword: Necessary learning / Elisabeth Soep.
Includes bibliographical references and index.
Keywords: Youth -- Political activity -- United States